Village Infrastructure Development Supervision Model (Study on the Optimization of BPD Supervision Function in Village Infrastructure Development) - Rudiansah, Bambang (Universitas Sultan Ageng Tirtayasa, 2025)
This research is motivated by the suboptimal supervision of the rural development strengthening program in Rancatungku Village, Pameungpeuk District, Bandung Regency. Based on that background, the researcher identified the problem of how the supervision process of the rural development strengthening program in Rancatungku Village is conducted. The theory used in this research is the types of supervision theory from Effendi (2018:211), which includes 3 dimensions: preliminary control, concurrent control, and feedback control. The method used is a qualitative descriptive research method with data collection techniques in the form of observation, interviews, and documentation. Based on the research results, it shows that the supervision of the Rural Development Strengthening Program in Rancatungku Village, Pameungpeuk District, Bandung Regency, based on the Bandung Regent Regulation Number 31 of 2014 concerning the Implementation of the Rural Development Strengthening Program, has not been optimal due to the existence of infrastructure development that has not yet been realized.